Climate change mitigation strategies by altering crop canopy for enhancing heat unit efficiency and sustainable productivity of sesame (Sesamum indicum L.): Climate change mitigation strategies by altering crop canopy for enhancing heat unit efficiency and sustainable productivity of sesame (Sesamum indicum L.) - C HARISUDAN (Journal of Oilseeds Research, 2020)
Field experiments on climate mitigation strategies for enhancing heat unit efficiency and productivity of sesame was conducted during summer 2016 at Regional Research Station, Vridhachalam. The treatment involved terminal nipping and 100 ppm salicylic acid spray at 30 and 45 DAS alone and in combination. The results of the experiments revealed that altering the crop canopy architecture by terminal nipping and foliar spray of 100 ppm salicylic acid at 30 DAS increased the heat unit efficiency and sesame seed yield.